Application of artificial intelligence to build a security control software system in local military units - Diep, Nguyen Khac; The, Nguyen Trong; Tra, Duong Xuan (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
This paper introduces the application of artificial intelligence to build a security control software system in local military units. This software system uses state-of-the-art convolutional neural networks (CNN SOTA) for facial recognition by testing two of the best facial recognition models currently available: the FaceNet model and the VGGFace model. Through testing on the proposed hardware, the FaceNet model meets the accuracy and speed requirements for practical application. The software includes multiple identity management categories to ensure information security and monitor the access of soldiers and other individuals. Additionally, the software features access management functions for protected areas, allowing for audio and visual alerts to ensure safety and security in those areas. The software also enables users to set up connections with other devices for efficient data collection and processing. Simultaneously, it supports synchronized data connection to help users save time and effort in managing information. Moreover, the software includes user-friendly interfaces and customizable settings, ensuring ease of use and adaptability to the specific needs of each military unit. this software system provides a comprehensive and effective solution for ensuring security and monitoring access in local military units. By leveraging artificial intelligence, the system can adapt and improve over time, offering enhanced performance and capabilities to meet the evolving security needs of military organizations. The innovative approach presented in this paper has the potential to significantly improve the overall security and efficiency of local military units, contributing to the safety and well-being of both military personnel and the communities they serve.